IDENTIFIKASI MASALAH PELAKSANAAN BELAJAR DARI RUMAH DI MASA PANDEMI COVID-19 PADA MATA PELAJARAN MATEMATIKA KELAS III DI SDN 2 BATUJAI - Mala Pazira; Siti Istiningsih; Muhammad Turmuzi (Program Studi PGSD, FKIP, Universitas Mataram, 2022)
Implementation of Learning From Home (BDR) is one alternative or action taken to continue to provide children's learning rights. With the implementation of learning with the BDR method, there are several problems in its implementation. The problem raised in this study is to identify the problem of implementing learning from home during the Covid-19 pandemic in Class III Mathematics at SDN 2 Batujai. The purpose of this study was to find out what are the problems with implementing learning from home during the covid-19 pandemic in class III mathematics at SDN 2 Batujai. The results of this study are expected to be used theoretically for teachers, for researchers, and for other researchers. The type of research used in this research is descriptive quantitative. The sampling technique used in this research is Nonrobability Sampling with saturated sampling type, where the sample uses all members of the population. The data collection technique in this study was the researcher using observation, interview and documentation techniques. The results of this study indicate that the withdrawal of the hypothesis based on the SPSS data table is Ha is accepted and Ho is rejected with a sig value. 0.031 < 0.05. Then there is the problem of implementing learning from the Covid-19 pandemic in class III mathematics subjects at SDN 2 Batujai.